In vitro propagation of Lippia integrifolia (Griseb.) Hier. and detection of genetic instability through ISSR markers of in vitro-cultured plants - Iannicelli, Jesica (2016)
Aromatic and medicinal plants have been traditionally harvested from the wild and, in Argentina, they have been exploited without any major limitation. In vitro plant propagation is an easy and inexpensive method to obtain huge amounts of plants in a short period. This practice is relevant for the propagation of valuable and endangered species, facilitating their conservation and germplasm breeding. Since tissue culture can induce genetic and phenotypic variations, collectively termed “somaclonal variation”, molecular markers have been used to determine the genetic variability induced. In this work, successful propagation of Lippia integrifolia (Gr.) Hie (“incayuyo”) was achieved with 2,2 μM of bencylaminopurine added to the Murashige-Skoog medium. Shoots were recovered from the development of axillary meristems and through de novo shoots regeneration from organogenic calluses. Regenerated plants were taken to an experimental trial nearby their natural habitat for their evaluation in an agricultural environment. From the moment phenotypic variants started to appear in the ex vitro regenerated plants, the genetic variability of both kinds of recovered materials was studied by intersimple sequence repeats. Thirteen markers were used, detecting polymorphisms with all the primers tested in both types of recovered plants. The existence of polymorphisms implies that the genetic stability must be evaluated in all the ex vitro recovered plants. The protocol developed here is the first step to be applied in biotechnological techniques employed to improve the quality of “incayuyo”. Moreover, this is the first work employing molecular markers in L. integrifolia.